Analysis of Capsicum annuum L. Methanolic Extract and Its Potential as a Hepatoprotector - Mustofa Helmi Effendi; Mohammad Sukmanadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
ThinLayerChromatography(TLC) method performed to purify capsaicin compound in C. annum L. and test the bioactive component of Capsicum Annum L on MAPK1 target proteins using the Immunohistochemistry (IHC) method to determine the reactions between receptor-ligand (antigen-antibody) complexes formed and become a reference in vivo tests. Natural ingredients need to be extracted to get some or all of the active ingredients used to synthesize the right dosage, easily stored, and maintain for a long time. The active ingredient of capsaicin is efficacious as a stimulant of gastric acid secretion and prevents infections in the digestive system.The immunohistochemical examination is intended to determine the expression of MAPK1 (ERK) on cells of mice hepatocytes (Mus musculus). MAPK 1 (ERK) expression score data were obtained using the modified Remmele method is the result of multiplying the percentage score of immunoreactive cells with the color intensity score on immunoreactive cells. The abnormal target protein signaling pathway contributes to cell proliferation, differentiation, survival, and uncontrolled cell apoptosis.Analysis of amino acid residues, Capsaicin to MAPK1haverelativelysimilarresiduessothatitcanbeconcludedthat the binding sites of the two compounds are close to similarities and affect receptors at relatively similar sites, namely oncogenicreceptors/ proteins. Concluded that the ethanol extract of Capsicum. annum L. had a greater in the powder form , TLC method showed the capsaicin standard was 1020 µg/ml, that capsaicin in chilies (Capsicum Annum L.) can synergistically inhibit cell through reactions in the anti-apoptotic MAPK 1 potentiates the antiproliferative action that can promote hepatoprotector, a finding that demands further clinicaltesting.